Pre-service Teachers’ Attitudes Toward Including Students with ASD in General Education - Houser, Mary A.; Guerriero, Tara S.; Bolton, David L.; Smidt, Esther (Journal of the American Academy of Special Education Professionals, 2022)
The purpose of this study was to examine special education and general education pre-service teachers’ attitudes toward including PK-12 students with autism spectrum disorder (ASD) in the general education classroom from an academic perspective. This study surveyed 160 undergraduate pre-service teachers (special education and general education) from a mid-size, northeastern state university’s teacher preparation programs using an adapted version of the Attitudes Toward Inclusive Education Scale (ATIES). Significant differences were found in preservice teachers’ attitudes when examining the impact of the academic level of the PK-12 student with ASD, the academic program of study (e.g. special education vs. general education), and the level of undergraduate progress (i.e. year in undergraduate career).